Solve for ż in the following equation: 1 – iz=-1 +iz (where i? = -1). Simplify your answer as much as possible.​

Question

Solve for ż in the following equation: 1 – iz=-1 +iz (where i? = -1). Simplify your answer as much as possible.​

in progress 0
Gerda 6 months 2021-07-17T16:09:31+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-07-17T16:10:34+00:00

    Answer:

    z = -i

    Step-by-step explanation:

    1 – iz=-1 +iz

    Add iz to each side

    1 – iz+iz=-1 +iz+iz

    1 = -1 +2iz

    Add 1 to each side

    1+1 = -1+1 +2iz

    2 = 2iz

    Divide by 2

    2/2 = 2iz/2

    1 =iz

    Divide by i

    1/i = iz/i

    1/i =z

    Multiply the left by i/i

    i/i^2 = z

    i/-1 =z

    -i =z

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )